Hepatitis E Virus Induces Hepatocyte Apoptosis via Mitochondrial Pathway in Mongolian Gerbils - Yang, Yifei; Shi, Ruihan; Soomro, Majid H.; Hu, Fengjiao; Du, Fang; She, Ruiping (Frontiers in Microbiology, 2018)
Previous studies demonstrated that Mongolian gerbils can be infected by hepatitis E virus (HEV), which induces the hepatic injury. Here, the mitochondria in hepatocytes from HEV-infected gerbils were considerably swollen, thin cristae. After HEV infection, the activity of superoxide dismutase (SOD) significantly decreased (p<0.01), while malondialdehyde (MDA) concentrations significantly increased, compared with those in the control group (p<0.01). Adenosine triphosphatease (ATPase) levels decreased significantly in the hepatocyte of the inoculated groups, compared with those in control group (p<0.05) at day 21 post-inoculation (dpi), 28dpi and 42dpi as well. Furthermore, the levels of ATP synthetase ATP5A1 significantly decreased during HEV infection, compared with those in the control group (p<0.05). According to the TdT mediated dUTP nick end labeling (TUNEL) detection, TUNEL positive hepatocytes increased in the inoculated group, compared with that in the control group (p<0.05). Up-regulation of the mitochondrion-mediated apoptosis regulating proteins, Bax and Bcl-2, in the HEV-infected gerbils (p<0.05) was observed. However, cytochrome c levels in mitochondria decreased, while this molecule was detected in the cytoplasm of the infected animals, in contrast to that in the control group. Apaf-1, and active caspase-9 and -3 levels were shown to be significantly higher in the inoculated group compared with those in the control group (p<0.05). Taken together, our results demonstrated that HEV infection induces hepatocyte injuries and activity of the mitochondrial apoptotic pathway, which trigger the hepatocyte apoptosis in Mongolian gerbils.